DC-SIGN Polymorphisms Associate with Risk of Hepatitis C Virus Infection Among Men who Have Sex with Men but not Among Injecting Drug Users. (13th November 2017) - Steba, Gaby S; Koekkoek, Sylvie M; Vanhommerig, Joost W; Brinkman, Kees; Kwa, David; Van Der Meer, Jan T M; Prins, Maria; Berkhout, Ben; Tanck, Michael; Paxton, William A; Molenkamp, Richard; Schinkel, Janke; et al.
Abstract : We identified a number of single nucleotide polymorphism (SNPs) in the DC-SIGN promoter region associate with risk of hepatitis C virus transmission via sexual exposure but not via intravenous drug use, and that the SNPs decreased promoter activity. Abstract: We aimed to identify whether genetic polymorphisms within L-SIGN or DC-SIGN correlate with hepatitis C virus (HCV) susceptibility. A men who have sex with men (MSM) and an injecting drug users (IDU) cohort of HCV cases and multiple-exposed uninfected controls were genotyped for numerous L-SIGN and DC-SIGN polymorphisms. DC-SIGN single nucleotide polymorphisms (SNPs) −139, −871, and −939 correlated with HCV acquisition in the MSM cohort only. When the same SNPs were introduced into a transcription activity assay they demonstrated a reduction in expression with predicted alteration in binding of transcription factors. DC-SIGN promoter SNPs correlated with risk of HCV acquisition via sexual but not IDU exposure, likely through modulation of mRNA expression levels.